Decolonization of Domestic Violence Interpretation in Contemporary Indonesia: Challenging Misogynistic Interpretations in QS. An-Nisa: 34 - Agus Handoko; Zakaria Abdiwali Mohamed (Tribakti: Jurnal Pemikiran Keislaman, 2026)
Domestic violence remains a persistent crisis in Indonesia, sustained not only by socio-economic pressures and gender inequality but also by religious discourses that normalize male authority within marriage. This article examines how Qur’anic interpretation, especially Surah An-Nisa verse 34, has been repeatedly used to justify gender hierarchy and, in some contexts, to legitimate coercion and violence against wives. The study employs a qualitative literature-based design that integrates critical hermeneutics, discourse analysis, and comparative exegesis, informed by feminist hermeneutics and decolonial theory. The findings show that dominant classical tafsir constructs qawwamun as inherent male leadership, reduces nushuz to a wife’s disobedience, and accepts daraba as regulated but permissible physical discipline. Together, these interpretations create an epistemic framework that renders domestic violence morally intelligible and socially governable through patriarchal household norms. In contrast, contemporary Indonesian reinterpretations advanced by Musdah Mulia and Faqihuddin Abdul Kodir reframe the verse through justice, reciprocity, and the protection of life and dignity, thereby rejecting violence as ethically incompatible with Qur’anic objectives. This article argues that such progressive tafsir constitutes a project of epistemic decolonization because it challenges the universalization of historically contingent patriarchal exegesis and repositions interpretive authority within context-sensitive ethical reasoning grounded in women’s lived realities. Theoretically, the study contributes to Qur’anic studies and gender justice scholarship by conceptualizing feminist tafsir as a decolonial intervention rather than a simple alternative reading, while also offering a faith-based epistemic foundation that strengthens legal advocacy and supports the implementation of Indonesia’s Domestic Violence Law.